The Law of the Sea and ASEAN: a comment / Salleh Omar (Universiti Teknologi MARA, Terengganu, 1991)
This paper takes a brief look at the yet to be ratified 1982 Law of the Sea Convention - an international treaty that is expected to reshape the present unsatisfactory and inadequate legal order governing the use of the seas. The Convention seems to offer the most appropriate avenue for the pacific settlement of the various disputes relating to the use of the seas in Southeast Asia in line with the aspirations of ASEAN. By adopting the provisions of the Convention as a basis for regional co-operation, ASEAN would reap good returns as this would enable it to jointly exploit its rich marine resources and also strengthen its bargaining positions as a unified bloc in future forums relating to the operation of the Convention.